Subgrid‐scale cloud–radiation feedback for the Betts–Miller–Janjić convection scheme. (2nd February 2016) - Koh, Tieh‐Yong; Fonseca, Ricardo
Abstract : Cloud–radiation feedbacks play a crucial role in the climate system and continue to be a major source of uncertainty in global climate model projections. Despite its importance for regional and local circulations, these feedback processes are not included in subgrid‐scale convective parametrizations used in regional weather and climate models, in particular in adjustment schemes that, as opposed to mass‐flux schemes, do not deal with convective condensates. Here we present a cloud scheme developed for the Betts–Miller–Janjić (BMJ) cumulus scheme used in the Weather Research and Forecasting (WRF) model that is fully general and can easily be applied to any other convective scheme. We parametrize the convective cloud fraction as a function of the BMJ time‐step precipitation rate with the vertical cloud profile given by a 'top‐heavy' Poisson distribution, similar to observed profiles. The cloud condensates are defined based on the assumption that the mass of convective cloud per unit mass of water vapour in cloudy air is constant in the column. In this scheme there are two tunable parameters: δ, that determines the vertical structure of the convective cloud, and γ, that controls the amount of cloud mass. The performance of the scheme is evaluated in a 1‐year run and WRF is found to give a much better representation of the observed cloudiness with smaller biases in the surface radiation fields with respect to observations and reanalysis.